Bacillus thuringiensis israelensis (Bti) for the control of dengue vectors: systematic literature review. Issue 5 (26th March 2013) - Boyce, R.; Lenhart, A.; Kroeger, A.; Velayudhan, R.; Roberts, B.; Horstick, O.
Abstract: Objective: To systematically review the literature on the effectiveness of Bacillus thuringiensis israelensis ( Bti ), when used as a single agent in the field, for the control of dengue vectors. Method: Systematic literature search of the published and grey literature was carried out using the following databases: MEDLINE, EMBASE, Global Health, Web of Science, the Cochrane Library, WHOLIS, ELDIS, the New York Academy of Medicine Gray Literature Report, Africa‐Wide and Google. All results were screened for duplicates and assessed for eligibility. Relevant data were extracted, and a quality assessment was conducted using the CONSORT 2010 checklist. Results: Fourteen studies satisfied the eligibility criteria, incorporating a wide range of interventions and outcome measures. Six studies were classified as effectiveness studies, and the remaining eight examined the efficacy of Bti in more controlled settings. Twelve (all eight efficacy studies and 4 of 6 effectiveness studies) reported reductions in entomological indices with an average duration of control of 2–4 weeks. The two effectiveness studies that did not report significant entomological reductions were both cluster‐randomised study designs that utilised basic interventions such as environmental management or general education on environment control practices in their respective control groups. Only one study described a reduction in entomological indices together with epidemiological data, reporting one dengue case in the treated area compared to 15 dengue cases in the untreated area during the observed study period. Conclusion: While Bti can be effective in reducing the number of immature Aedes in treated containers in the short term, there is very limited evidence that dengue morbidity can be reduced through the use of Bti alone. There is currently insufficient evidence to recommend the use of Bti as a single agent for the long‐term control of dengue vectors and prevention of dengue fever. Further studies examining the role of Bti in combination with other strategies to control dengue vectors are warranted.